The Turbidity, pH, Direct Gram as Predictors of Symptomatic Urinary Tract Infections in Pregnant Women - Dhian Karina Aprilani Hattah; Rizalinda Sjahril; Sriwijaya Sriwijaya (Nusantara Medical Science Journal, 2022)
Introduction: Urinary tract infections (UTIs) are common in the community, including among pregnant women. This study investigates turbidity, urine pH, and direct gram as predictors of symptomatic urinary tract infection in pregnant women. Methods:  A total of 177 pregnant women with suspected UTIs based on clinical and laboratories at the community health center in Makassar were collected from September to December 2021. The Urine sample was assessed for turbidity, urine pH, direct gram, and urine culture. Results: Urine turbidity was found in 108 (75.5%) patients who had positive cultures and PPV of 94.7%. The mean pH of the urine from UTI patients was 6.42 and without UTIs was 6.45. Urine that grows Gram-positive bacteria showed the most alkaline pH (mean pH=6.71) and was significantly less acidic than urine with UTI negative. In contrast, urine with Gram-negative bacteria had the most acidic pH (mean PH=6.30). The gram direct test shows a significant association with UTIs.  Conclusions: Turbid urine can predict urinary tract infections in pregnant women that provide clinical symptoms. In addition, leukocytes esterase test further selected the samples. Urine pH showed no significant correlation with UTI. Less acidic urine pH is particularly associated with Gram-positive bacterial infections. Furthermore, direct gram can predict the event of UTI.